Bioavailability and Bioefficacy of Hemp By-Products in Ruminant Meat Production and Preservation: A Review - Semwogerere, Farouk; Katiyatiya, Chenaimoyo L. F.; Chikwanha, Obert C.; Marufu, Munyaradzi C.; Mapiye, Cletos (Frontiers in Veterinary Science, 2020)
Plant by-products obtained from agro-industrial processes require valorisation to demonstrate their potential for enhancing animal health, meat production and shelf life extension. One example is the fast-growing hemp industry, which produces seeds, leaves, seed oil and cake. Studies on the nutritional value of hempseed cake have shown it can be a valuable source of protein in ruminant diets. However, there is limited documentation on the bioavailability and bioefficacy of hemp phytochemicals for improving ruminant health, production and extending meat shelf life. The current review provides an overview of existing information on nutrient and phytochemical composition of hemp by-products, their bioavailability and bioefficacy, and explores current limitations and prospects regarding their valorisation.